Sinaiella azadi sp. nov. (Mantodea: Toxoderidae); a new praying mantis species from Western Asia (Iran and Armenia) - Kolnegari, Mahmood; Schwarz, Christian J.; Ghrejyan, Tigran; Borer, Matthias (Zootaxa, 2025)
The Mantodea fauna of Iran comprises nine families and at least 40 species. Scientific surveys conducted by Iranian entomologists have recently led to an increased knowledge on the diversity and biology of mantises. Among the Mantodea species dispersed in Iran, the family Toxoderidae has been regarded as a group of highly cryptic praying mantids with greatly elongated bodies in common. Up to now, six species of this family have been reported from Iran, entirely from the southern half of the country. Herein, we describe Sinaiella azadi sp. nov. from the Markazi Province, in central Iran. Moreover, our ex-situ investigation led to the identification of this new species from a preserved collection in Armenia. These findings considerably extend the known distribution of the genus Sinaiella Uvarov, 1924 beyond the Arabian Peninsula. We also discuss the genus and include a proposed dichotomous key to the Sinaiella species.